PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MODERASI (Studi pada pelanggan Brownies Amanda Surakarta Cabang Nusukan) - Arif Dwi Putranto; Suprihatmi Sri Wardiningsih; Suprayitno Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
One of the factors that make loyal customers against brownies Amanda is a quality product. So is the case with product quality, service quality, promotion and customer satisfaction which can support customer loyalty. The population in this research is the customers Brownies Amanda Surakarta. Sample numbering 100 respondents with the formula Leedy. The technique of sampling was done randomly sampling with a deliberate method of sampling. Test instrument use test validity and reliability tests, methods of data analysis using classical assumptions of the test, a multiple linear regression analysis, t-test, F-test and coefficient of determination (R2) and the absolute difference test. The results of this study showed that the quality of products, quality of service, promotions and customer satisfaction in partial effect significantly to loyalty customer loyalty Brownies Amanda Surakarta. Customer satisfaction the moderating influence of the quality of products, quality of service, promotions and customer satisfaction are partial toward customer loyalty Brownies Amanda Surakarta. Results the coefficient of determination (adjusted R2) of 0,732, which means that the magnitude of the contribution to the influence of the variable quality of products, quality of service, promotions and customer satisfaction towards loylitas customers Brownies Amanda Surakarta is 73,2%, While the rest of 26,8% is affected by other variables not examined.Keywords: product quality, service quality, promotion. customer loyalty, customer satisfaction.